A nonclassical pathway of β-hematin crystal nucleation enables its suppression by antimalarials - Wenchuan Ma; Lakshmanji Verma; Huan-Jui Lee; Weichun Pan; Michael B. Sherman; David J. Sullivan; Jeffrey D. Rimer; Jeremy C. Palmer; Peter G. Vekilov (Communications Chemistry)
Abstract Organic biocrystals support essential functions or drive pathologies in numerous living organisms. Here we focus on the nucleation of hematin crystals, which form in malaria parasites as a part of their heme detoxification pathway. Suppression of hematin crystal nucleation has proven the most productive strategy to treat malaria, yet little is known about the relevant molecular mechanisms. We show that crystal nucleation can be suppressed and fine-tuned via the properties of a population of precursors that host nonclassical hematin crystal nucleation. The addition of modifiers selectively invokes one of three outcomes: suppressed nucleation, faster nucleation, or no effect. We demonstrate that β-hematin crystal nuclei form within mesoscopic hematin-rich clusters and that the impacts of the modifiers on crystal nucleation parallel their activity towards the nucleation precursors. Molecular simulations reveal that modifiers’ activities derive from their interactions with the hematin monomers, dimers, and larger agglomerates. Collectively, these observations support a general method to control crystal nucleation that relies on solute-modifier interactions and their consequences for the nucleation precursors. The proposed rationale offers a powerful tool to control nucleation in areas that employ tailored crystalline materials and helps to understand how crystal assemblies with elaborate superstructures appear in nature.